2017
DOI: 10.1111/ajco.12765
|View full text |Cite
|
Sign up to set email alerts
|

Cancer multidisciplinary team meetings in practice: Results from a multi‐institutional quantitative survey and implications for policy change

Abstract: Aim: Multidisciplinary care is advocated as best practice in cancer care. Relatively little is documented about multidisciplinary team (MDT) meeting functioning, decision making and the use of evidence to support decision making in Australia. This descriptive study aimed to examine team functioning, the role of team meetings and evidence use in MDTs whose institutions are members of Sydney Catalyst Translational Cancer Research Centre. Methods:We designed a structured 40-item survey instrument about topics tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 40 publications
(32 reference statements)
1
77
0
Order By: Relevance
“…Given the widespread adoption of different EMR systems in hospitals across the world, it is surprising that MDT presentations are often not embedded within this system but exist as separate files, often in free‐text form. Details of MDT discussions and decisions are recorded inconsistently, and salient discussion points may be missing . The lack of important details can be an issue during recall, or worse, if there were a medicolegal enquiry on the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the widespread adoption of different EMR systems in hospitals across the world, it is surprising that MDT presentations are often not embedded within this system but exist as separate files, often in free‐text form. Details of MDT discussions and decisions are recorded inconsistently, and salient discussion points may be missing . The lack of important details can be an issue during recall, or worse, if there were a medicolegal enquiry on the case.…”
Section: Discussionmentioning
confidence: 99%
“…Details of MDT discussions and decisions are recorded inconsistently, and salient discussion points may be missing. 19 The lack of important details can be an issue during recall, or worse, if there were a medicolegal enquiry on the case. Apart from the primary clinician in charge, the concerned MDT members who participated in the discussion and treatment decisions can be potentially culpable.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have evaluated and reported the responses of lung cancer MDT members to data presentation and feedback using a mixed‐methods approach. Several studies investigate aspects of MDT practice (from lung cancer and other streams), including processes, reporting to general practitioners, data characteristics, and timing of MDT discussion . The systematic review by Prades et al includes three papers that focus on aspects of lung cancer MDT care.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies reported on data feedback to the MDT although two performed analyses on data collected by the MDT or the local clinical cancer registry. Rankin et al surveyed 37 Australian MDTs across a range of tumor streams on MDT purpose, processes, caseload, and quality assurance and identified the potential lack of access to databases for key information on patient population. A mixed‐methods study of a lung cancer MDT‐reporting template for general practitioners identified a data set that general practitioners found easy to interpret and communicate to their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation